The brefeldin A resistance protein Bfr1p is a component of polyribosome-associated mRNP complexes in yeast - Lang, Brian D. (Oxford University Press, 2001)
The yeast gene BFR1 was originally isolated from a genetic screen for high-copy suppressors of brefeldin A-induced lethality in Saccharomyces cerevisiae. While this result suggested a possible role for the encoded protein, Bfr1p, in the secretory pathway, subsequent data have not fully supported this conclusion. Alternatively, Bfr1p has also been found by yeast two-hybrid analysis to interact with Bbp1p, a component of the spindle pole body. Finally, we have reported that Bfr1p associates with cytoplasmic mRNP complexes containing Scp160p, raising the possibility that Bfr1p may function in mRNA metabolism. Here, we have explored this possibility further. We report that Bfr1p associates with yeast polyribosomes and mRNP complexes even in the absence of Scp160p, and that its interaction with Scp160p-containing mRNP complexes is RNA-dependent. Furthermore, we have determined by fluorescence microscopy and subcellular fractionation that Bfr1p and Scp160p demonstrate similar cytoplasmic localization with enrichment around the nuclear envelope/endoplasmic reticulum. Finally, we report that loss of Bfr1p disrupts the interaction of Scp160p with polyribosomes, thereby demonstrating that the relationship between these two proteins is functional as well as physical. Considered together, these data raise the intriguing possibility that Bfr1p may provide a link between mRNA metabolism, the chromosomal segregation machinery and perhaps secretion in yeast.